ANALYSIS THE PRICING PERSPECTIVE BETWEEN NORMAL AND PACKAGE PRICE OF KARTU AS TELKOMSEL - Soelama, Pricilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
ABSTRACT Regarding with potential contributions of price for enhancing products selling or services utilization in the marketplace, one vital approach from price concept usually used by many marketers is pricing strategy concept. This applied model can be established by three main concepts, which are cost considerations concept, competitive consideration concept, and consumer consideration. Two research objectives are to examine significant differences in pricing between normal and package price and between female and male users for normal and package price of Kartu As Telkomsel. Theories supporting in this research are related to price and pricing. The population is users of Kartu As with sample research as many as 100 respondents and using convenience sampling design. Results and conclusions show that there is a significant difference in pricing perspective between normal and package price and no significant differences in pricing perspective between male and female of Kartu As Telkomsel. Keywords: price, pricing strategy